Leaf blight and stem rot disease infection on eucalyptus (Eucalyptus pellita) - Ayu Safitri; Gusti Apriliansyah; Yuniar Harvianti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2026)
Eucalyptus pellita is an important plant for the pulp and paper industry. During its growth and development process, there are factors that inhibit Eucalyptus, namely stem rot and leaf blight caused by Ceratocystis and Cylindrocladium. The purpose of this study was to determine the incidence and intensity of leaf blight and stem rot diseases caused by Ceratocystis and Cylindrocladium, as well as to identify the ecological conditions and disease distribution in the Baung Central Nursery and Sungai Beyuku Nursery areas. The observation method used was direct field observation with purposive sampling and interviews with representatives from the nursery division. Symptoms of stem rot caused by Ceratocystis are indicated by streaks or lines that appear as pale brown to blackish patches on the sapwood, which result in weakened and broken stems. Symptoms of leaf blight caused Cylindrocladium include round or oval dark brown to blackish leaf spots, which in advanced stages spread to the underside of the leaf and turn black. This study concludes that disease incidence in Baung Central Nursery is dominated by leaf blight caused Ceratocystis, while in Sungai Beyuku Nursery it is dominated by leaf blight caused by Cylindrocladium.